PENGARUH PENERAPAN LAUGHTER YOGA TERHADAP TINGKAT STRES IBU RUMAH TANGGA DI DUSUN TAWANG SARI KECAMATAN SEMEN KEDIRI - Agustin Widyowati; Dewi Novita Sari (JURNAL SABHANGA, 2020)
Introduction : A mother’s busyness can have an impact on physical and psychological disorders if not addressed properly. In psychological disorders can cause stress. One of the stress management skills was laughter yoga. The purpose of the research was to knew the effect of yoga laughter application on housewife stress level in tawang sari sub-district semen Kediri. Method : The research used by pre-experimental design (one group pre-post test). The research population was all housewives in Tawang Sari Hamlet, Semen Subdistrict, Kediri. Sample was taken using purposive sampling techniques as much 38 respondent. The independent variable was yoga laughter application and the dependent variable was housewife stress level. Data collection using questionnaire sheets and analyzed by wilcoxon test. Result : The results showed that almost half of the housewives before being given the application of laughter yoga experienced moderate stress (34.2%) while after being given the application of laughter yoga experienced mild stress levels as many as 16 respondents (42.1%). Sig p value (0,000) less than 0,05, H1 was accepted, meaning there was the effect of the application of laughter yoga on the stress level of housewives. Conclusion : The conclusion of this research was application of laughter yoga can have one solution for housewives stress management they experienced.